Clean-Label Strategies for the Replacement of Nitrite, Ascorbate, and Phosphate in Meat Products: A Review - Minhyeong Kim; Su Min Bae; Yeongmi Yoo; Jibin Park; Jong Youn Jeong (Foods, 2025)
The clean-label movement has markedly increased consumer demand for meat products free from synthetic additives, such as sodium nitrite, ascorbate, and phosphate. This review summarizes strategies to replace these additives with natural alternatives while preserving the functional and quality properties of traditionally cured meats. Nitrite replacement commonly employs nitrate-rich vegetables, alongside nitrate-reducing starter cultures or pre-converted nitrite powders for adequate nitric oxide production and meat pigment stabilization. Ascorbate substitutes include vitamin C-rich materials and polyphenol-based antioxidants from green tea and rosemary, supporting nitrite reduction and contributing to meat pigment and oxidative stability. To compensate for phosphate functions, natural substitutes such as hydrocolloids, dietary fibers, protein isolates, and calcium powders from eggshells or oyster shells have shown partial success in restoring water-holding capacity, pH buffering, and textural integrity. In addition, non-thermal processing technologies, such as high-pressure processing, ultrasound, and cold plasma are explored as complementary strategies to enhance the efficacy of natural ingredients and support industrial scalability. However, challenges persist regarding ingredient variability, dose-dependent effects, and consistency in functional performance. Future research should focus on synergistic ingredient combinations, formulation standardization, and scalable application in industrial production to ensure the production of high-quality clean-label meat products.